2017
DOI: 10.14499/indonesianjpharm28iss2pp74
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity of 2,5-Bis(4-Boronic Acid)benzylidine Cyclopentanone on Her2 Overexpressed-Cancer Cells

Abstract: Development of chemotherapeutic agent and boron carrying pharmaceutical based on HER2 specific targeted is important due to its role in enhancing cancer progression. The purpose of this study is to synthesize curcumin analogue, namely Pentagamaboron-0 (PGB-0) or 2,5-bis(4-boronic acid)benzylidine cyclopentanone, and to explore the cytotoxic activity on HER2 overexpressed-cancer cells. MCF-7/HER2 was used as a model of HER2 overexpressed-cancer cells and NIH3T3 as normal cells. PGB-0 bound to ATP binding site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Previous study showed that PGB-0-F as an anti-cancer agent which has cytotoxic effect of 4T1 cells with IC 50 values of 33 µM (Meiyanto et al, unpublished data), while PGB-0 has IC 50 value of 300 µM in 4T1 cells (Kusumastuti et al, unpublished data), and 270 µM in MCF-7/Her2 cells (Utomo et al 2017). In this present study, we also observed the inhibition of cancer cell migration as the one of parts of metastasis process by treatment of PGB-0-F through scratch wound healing assay.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous study showed that PGB-0-F as an anti-cancer agent which has cytotoxic effect of 4T1 cells with IC 50 values of 33 µM (Meiyanto et al, unpublished data), while PGB-0 has IC 50 value of 300 µM in 4T1 cells (Kusumastuti et al, unpublished data), and 270 µM in MCF-7/Her2 cells (Utomo et al 2017). In this present study, we also observed the inhibition of cancer cell migration as the one of parts of metastasis process by treatment of PGB-0-F through scratch wound healing assay.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, K-PGV-0, a soluble form of PGV-0 also performed anti-migratory effect on highly metastasis breast cancer (Putri et al 2016). Dibenzilidine boronic acid cyclopentanone (DBBAC) or pentagamaboronon-0 (PGB-0) is a novel boron containing-curcumin analog which is designed and synthesized by Cancer Chemoprevention Research Center, Universitas Gadjah Mada based on the benzylidine cyclopentanone structure (Utomo et al 2017). This compound has been explored for the anticancer activity and boron carrying pharmaceutical for BNCT (Boron Neuton Capture Therapy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study reveals that PGB-0 have cytotoxic activity on MCF-7/ HER2 breast cancer cells by modulated cell cycle in G1 phase. This activity is thought to be caused by binding of PGB-0 in the tyrosine kinase part of HER2 as evidenced by a decrease in HER2 expression in PGB-0 treatment (Utomo, et al, 2017). PGB-0 in combination with doxorubicin also showed antimigration by decreased the MMP-9 expression on 4T1 cells (CCRC unpublised data).…”
Section: Introductionmentioning
confidence: 96%
“…The low cytotoxic effect (IC 50 > 200 μM) on HER2-expressed breast cancer cells, no toxic effect against normal fibroblast cells, and comparable with lapatinib and curcumin on the interaction with HER2 are the current modality of PGB-0 as novel boron carrier (5).…”
Section: Introductionmentioning
confidence: 99%